Chronic Cervicogenic Tinnitus Rapidly Resolved by Intermittent Use of Cervical Collar - Bechter, Karl; Wieland, Martin; Hamann, Gerhard F. (Frontiers in Psychiatry, 2016)
Introduction: Cervicogenic tinnitus is a not generally accepted pathogenetic subtype, which might be subsumed under the concept of somatosensory tinnitus. After the personal experience of therapy resistant tinnitus in context with a cervical pain syndrome (CS) and successful add-on treatment with cervical collar (CC), the idea was persued in several individual treatments in patients. Patients and Methods: Reporting one particular case with chronic tinnitus considered untreatable, but rapidly improved with CC use. Thereafter tinnitus was experimentally replicated by head inclination, the respective neck-head angles and cerebral blood flow measured. Results: Chronic subjective tinnitus of a 20 years duration completely disappeared within 4 weeks with an intermittent short time application of CC. Thereafter, tinnitus was liberately again induced by head inclination, set on with anterior tilt of 14°, reaching maximum strength by 23°. Tinnitus stopped with return to neutral head position. Blood flow in the vertebral arteries on both sides was unchanged during head inclination with prevalent tinnitus, however blood flow was physiologically reduced with head rotation though not accompanied by tinnitus. Discussion: In a single case of chronic tinnitus, we found that treatment with CC rapidly led to full remission. Nevertheless, tinnitus could be resumed by constrained head postures. Experimental tinnitus replication by inclination points to an underscored role of upper posterior cervical muscle groups, matching with animal experiments, working in concert with other triggers including psychological factors. Blood flow reduction in vertebral arteries was unrelated to tinnitus.